Experimental analysis of the performance of a new shipboard gravity gradient measurement system - Li, Rui; Li, Da; Shu, Qing; Fan, Zhenyu; Lu, Kai; Zhou, Jianxin; Zhang, Jiahong; Xu, Guangjing (Frontiers in Physics, 2023)
The gravity gradient tensor, which has a higher resolution than gravity, is used in a variety of fields, including the discovery of energy resources, auxiliary navigation, and national defense building. Our team has achieved significant advancements in various essential technologies, such as high-resolution accelerometers, and has constructed China's first self-controllable shipboard gravity gradient measurement system. In the laboratory, accuracy is determined using the mass gravitation technique. Static test accuracy is better than 7.22E@100s, while dynamic test accuracy is better than 9.09E@100s. For outfield shipborne test measurement, the internal accord accuracy of the repeat line is less than 27.3E@750m, and that of the intersection point is smaller than 28.8E@750m. The performance of the system is completely validated by dynamic and static testing, laying the groundwork for the practical implementation of gravity gradient technology.